MATLAB Answers

factor an expression into two expressions

1 view (last 30 days)
Ryan on 13 Mar 2012
I have a function a=3/(1+e*cos(f)) where both e and f are symbolic variables. I would like to write this function as the sum of two expressions B and G where a=B+e*G. For this example problem, I know that B=3 and G=(-3*cos(f))/(1+e*cos(f)). What commands in Matlab would allow me to write this expression in this form? Thank you.

Answers (0)

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!